2010
DOI: 10.1007/s00277-010-0980-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of microRNA-451 in normal and thalassemic erythropoiesis

Abstract: MicroRNAs (miRNAs) are negative regulators of gene expression that play an important role in hematopoiesis. Thalassemia, a defective globin synthesis leading to precipitate of excess unbound globins in red blood cell precursors, results in defective erythroid precursors and ineffective erythropoiesis. Expression pattern of miR-451, an erythroid-specific miRNA, was analyzed during differentiation of erythroid progenitors derived from normal and thalassemic peripheral blood CD34-positive cells, after 14 days of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 24 publications
3
24
0
Order By: Relevance
“…1c). Our results corroborate other results where thalassemic progenitors multiply more, but are slower in differentiation milestones, compared to their normal counterparts [7]. In our system the progenitor cells of normal donors multiplied ∼100 times, but in thalassemic individuals the increase is much greater.…”
Section: Figsupporting
confidence: 82%
“…1c). Our results corroborate other results where thalassemic progenitors multiply more, but are slower in differentiation milestones, compared to their normal counterparts [7]. In our system the progenitor cells of normal donors multiplied ∼100 times, but in thalassemic individuals the increase is much greater.…”
Section: Figsupporting
confidence: 82%
“…Roughly a third of thalassemia patients are b0/b0 (Dehghanifard et al 2013). The resulting imbalance between the globin chains leads to alpha-chain accumulation in erythroid cells and subsequently to hemolytic anemia and ineffective erythropoiesis (Svasti et al 2010). These patients depend on regular transfusions for survival, a treatment which in itself complicates their condition by iron overload and precipitation in issues such as heart and liver (Musallam et al 2012).…”
Section: Introductionmentioning
confidence: 98%
“…In addition, miR-451a was required for erythroid homeostasis [41]. Svasti S et al demonstrated that early erythroid progenitors in β-thalassemia have possessed a dysregulated miRNA-451a expression program [42].…”
Section: Oncotarget S474 Wwwimpactjournalscom/oncotargetmentioning
confidence: 99%